'It's the most important thing – I mean, the schooling': father involvement in the education of children with autism. Issue 4 (1st October 2016) - Potter, Carol
Abstract: Father involvement in education has been shown to result in a range of positive outcomes for typically developing children. However, the nature of paternal involvement in the education of children with disabilities and especially autism has been under-researched and is little understood. This study aimed to explore the nature of the involvement of 25 UK fathers in the education and their children with autism, aged up to 19 years through the use of semistructured interviews. Findings showed that fathers were highly engaged both directly and indirectly across several dimensions of their children's education and schooling. Key areas of indirect engagement were involvement in administrative processes necessary for securing an appropriate educational placement; facilitating daily access to school and general support of children's progress through attendance at school-based meetings and events. Direct support for learning occurred through homework assistance and working on school-related goal. Findings are discussed in relation to diversity and generative models of fatherhood. Implications for greater father inclusion in the education of children with autism are explored with reference to a gender-differentiated approach.